Cholestasis of pregnancy: a prospective analysis from a South Andaman teaching hospital - Pegu, Bhabani; Mehrotra, Manju; Yadav, Anita; Sahoo, Pinky S. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Intrahepatic cholestasis of pregnancy (IHCP) is one of the commonest pregnancy related liver disorder. Although the maternal course is usually benign, there is an increased risk of spontaneous preterm delivery, fetal compromise, meconium stained amniotic fluid and even intrauterine fetal demise. The objective of this study was to study the incidence of IHCP and its impact on maternal and perinatal outcome. Methods: A prospective study carried out in 68 number of IHCP cases. Diagnosis was done on the basis of clinical and laboratory parameters. All the cases were followed up to the puerperium to find out maternal and perinatal outcome. Results: The incidence of cholestasis of pregnancy was 2.73%. Most (88%) of the cases were presented with generalized pruritus, relived with ursodeoxycholic acid and complete recovery was observed after delivery. The rate of instrumental delivery was 8.82% and caesarean section rate was 30.88%. Most common indication of caesarean section was fetal distress and non-progress of labour. There was one stillbirth at 35 weeks however none of the mother had complication during labour or puerperal period. Conclusions: Increased level of liver enzymes in patients of IHCP associated with poor perinatal outcome. Therefore, careful monitoring during antenatal period and termination of pregnancy at term will result in favourable outcome of both mother and baby.